Strangulated intestinal obstruction caused by ectopic intrauterine device: a case report - Kaifu Zheng; Qian Zhang; Tiehu Wang; Xiaolu Zhu; Zhengping Li; Jinshui Chen (BMC Women's Health)
Abstract An intrauterine contraceptive device (IUCD) is a widely utilized contraceptive method. However, in rare instances, it may lead to severe complications such as strangulated intestinal obstruction. This paper presents a case involving an elderly female patient who developed acute abdominal pain and was subsequently diagnosed with strangulated intestinal obstruction attributed to an ectopic IUCD. The patient’s initial symptomatology included upper abdominal pain and severe vomiting, which led the clinician to perform only an upper-abdominal CT scan, yielding no significant findings. Following three days of conservative management, the symptoms persisted without relief. The patient continued to experience abdominal pain, accompanied by abdominal distension, and a cessation of both flatus and bowel movements. Consequently, a comprehensive abdominal CT scan was performed, revealing bowel obstruction with peritonitis. An urgent laparotomy was subsequently undertaken. Due to the necrotic condition of the bowel, a resection of the affected segment was performed, followed by a one-stage end-to-end intestinal anastomosis after the removal of the intrauterine device (IUCD). By the ninth postoperative day, the patient had recovered sufficiently to be discharged from the hospital. This case underscores the importance for women with an IUCD to regularly assess the device’s position and depth to prevent serious complications. It is also advisable to remove the IUCD promptly upon reaching the end of its effective lifespan or following menopause. Clinicians should be vigilant in monitoring and addressing abdominal pain in women with an IUCD.